2018
DOI: 10.1590/1807-1929/agriambi.v22n2p113-118
|View full text |Cite
|
Sign up to set email alerts
|

Growth, water use and efficiency of forage cactus sorghum intercropping under different water depths

Abstract: A B S T R A C TThe effects of the forage cactus sorghum configuration and different irrigation depths on the growth, water use and efficiency of the forage cactus production system were investigated in this study. The experiment was conducted in the municipality of Serra Talhada, Pernambuco State, Brazil, between the years 2012 and 2013. Forage cactus was distributed in randomized blocks with factorial scheme and four replicates, in split plots (5 x 2), with five irrigation depths (0, 8.75, 17.5, 26.25 and 35%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 17 publications
1
29
0
21
Order By: Relevance
“…Under adverse environmental conditions, sorghumlegume intercropping resulted in improved biomass production compared to mono cropping (Iqbal et al 2017). Sorghum-cactus pear intercropping showed higher water use efficiency under severe drought because of lower evapotranspiration, which resulted in improved biomass production (Lima et al 2018). Similarly, Diniz et al (2017) reported that sorghum was dominated by cactus pear in intercropping indicating a higher competitive capacity of cactus pear compared to sorghum.…”
Section: Strip Intercropping Systemsmentioning
confidence: 98%
“…Under adverse environmental conditions, sorghumlegume intercropping resulted in improved biomass production compared to mono cropping (Iqbal et al 2017). Sorghum-cactus pear intercropping showed higher water use efficiency under severe drought because of lower evapotranspiration, which resulted in improved biomass production (Lima et al 2018). Similarly, Diniz et al (2017) reported that sorghum was dominated by cactus pear in intercropping indicating a higher competitive capacity of cactus pear compared to sorghum.…”
Section: Strip Intercropping Systemsmentioning
confidence: 98%
“…Devido a importância da irrigação nas regiões áridas e semiárida, estudos com essa temática para espécies forrageiras vem evoluindo. De acordo com a literatura, alguns trabalhos já enfatizam a utilização de práticas de irrigação em culturas como a palma forrageira (Morais et al, 2017;Diniz et al, 2017;Lima et al, 2018a;Lima et al, 2018b).…”
Section: Prática De Irrigação Em Plantas Forrageirasunclassified
“…Na maioria das culturas agrícolas, a aplicação de água abaixo dos requisitos hídricos Research, Society and Development, v. 9, n. 7, e569974503, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4503 para máxima produção das culturas, aumenta a eficiência do uso da água (Medici et al, 2014;Li et al, 2018;Lima et al, 2018). Este fato é decorrente, por fornecer quantidades de irrigação abaixo do nível máximo de demanda por água da planta, visando rendimentos praticamente estáveis, permitindo economizar de 20 a 40% da água, acarretando em redução de rendimentos inferiores a 10% a depender da espécie e/ou cultivar (Davies et al, 2011).…”
Section: Redução Da Lâmina De Irrigaçãounclassified